Eligibility for dabigatran therapy: the real-life experience of a Tuscany general hospital - Pugi, Alessandra; Fallani, Francesca; Palazzi, Nadia; Banfi, Roberto (Recenti progressi in medicina, 2014)
Introduction. Dabigatran has emerged as a promising alternative to vitamin K antagonists (VKAs) in non-valvular atrial fibrillation (NVAF). It has several clinical and practical advantages over VKAs that finally facilitate their use in clinical practice. The aim of this study is to describe patients taking dabigatran, to evaluate its use in the real world and the eligibility for therapy, according to the criteria established by the Italian Medicines Agency (AIFA). Methods. A retrospective review was conducted using dabigatran prescriptions in patients with NVAF. Data were retrieved from the prescriptions recorded in the hospital pharmacy of Careggi General Hospital from June to October 2013. Results. Data were related to 138 patients with NVAF who have at least one dabigatran prescription. Patients have a mean age of 79.0 ± 8.9 years, mean CHA2DS2-VASc 4.4 ± 3.0 and mean HAS-BLED 3.0 ± 1.0. 49.3% were male and 50% were older than 80 years; 18.8% were treated with high-dose dabigatran (150 mg). According to the AIFA criteria, 85.5% of patients were eligible for treatment: 34% were at high embolic and bleeding risk and 70.2% reported objective problems in routine coagulation monitoring. Conclusions. Our patients can be categorized in two groups: subjects with high risk of embolism and bleeding for whom the new oral anticoagulant dabigatran provides clinically important benefit, and subjects for whom the benefit derives from a simplified management of therapy. It should be interesting to evaluate the rate of therapeutic adherence in these patients in order to verify the expected clinical benefits.